Sales Promotion dan Online Customer Review’s Terhadap Impulsive Buying Dazzle Me Pada Fitur Tiktok Shop - Tesalonika, Vichel Audrea; M, Madeleine; Salim, Jenice Prettycia; Wijaya, Virly (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this study is to find out how much influence Sales Promotion and Online Customer Review's on Impulsive Buying of Dazzle Me products on the Tiktok Shop application. The population in this study is TikTok application users who have purchased Dazzle Me products on the TikTok Shop application with samples determined through non-probability sampling techniques, namely purposive sampling with 100 respondents. The results of this study show that Sales Promotion and Online Customer Review's each partially have a significant positive effect on Impulsive Buying of Dazzle Me products on Tiktok Shop